Evaluating the Role of Jordanian Media Institutions in Raising Awareness of the Importance of Dialogue and Coexistence among Followers of Religions from the Perspective of Students of the University of Jordan - Al-Neimat , Amal Abdallah Mohammad (Dirasat: Shari’a and Law Sciences, 2021)
This study aims at evaluating the role of Jordanian media institutions in raising awareness of the importance of dialogue and coexistence among followers of religions from the perspective of students of the University of Jordan. The sample of the study consisted of (601) male and female students randomly selected from the School of Sharia and other schools. The study used a questionnaire to collect data after ensuring their authenticity and consistency according to presepcified criteria. The study used the descriptive approach by showing the importance of dialogue and coexistence between followers of different religions and the importance of awareness of these concepts. The extrapolation method was used by extrapolating the students’ opinions of the University of Jordan in their assessment of the role of Jordanian media institutions in deepening awareness of the importance of dialogue and coexistence between followers of religions. Moreover, it followed the analytical approach by analyzing the outputs of the questionnaire and indicating the most important results derived from it. The study revealed high results in students’ evaluation of media institutions for both of the variables of the study, and the absence of any significant differences at the level of (0.05≥α) in these variables based on gender or specialization. The study recommended the importance of conducting a study on the role of education curricula in establishing awareness of the values of dialogue and coexistence.